PERANCANGAN GAME EDUKASI VISUAL NOVEL BERTEMA PERUBAHAN IKLIM MENGGUNAKAN REN’PY BERBASIS PYTHON - Aria Cahya Diva; Ifan Junaedi; Anton Zulkarnain Sianipar (LPPM Universitas Abdurrab, 2025)
This study aims to design and develop an educational visual novel game themed around environmental and climate change issues using Ren'Py, a Python-based engine. The game was developed using the Game Development Life Cycle (GDLC) method, which consists of six stages: initiation, pre-production, production, testing, beta, and release. The test subjects consisted of 15 teenagers aged 14–16 years living in RT 14, Jalan Swadaya 1, Manggarai, South Jakarta. The trial results showed that the game successfully attracted user interest and effectively conveyed educational messages related to climate change issues. User evaluations indicated an increase in understanding of environmental topics, active engagement with the branching narrative, and an enjoyable learning experience through integrated minigames. The game is considered suitable for wider publication as an interactive and reflective digital learning medium for teenagers. In addition, functional testing using the blackbox testing method on 10 main features demonstrated that all features performed successfully (100% functionality achieved). Thus, this educational game is expected to serve as an alternative medium to help teenagers better understand the importance of environmental conservation and awareness of climate change impacts.